WAKTU SHALAT ASHAR, MAGHRIB DAN ISYA’ PERSPEKTIF HADIS - Farah, Labibah Amil (ELFALAKY: Jurnal Ilmu Falak, 2020)
AbstrackPrayer is the most important worship in Islam. Prayer is worship predetermined time and how. The jurists decide the time of prayer based on the rotation of the earth or natural phenomena. The determination of the time of prayer that occured on al-Qur’an and Sunnah needs to be explained using celestial cues and the thought of thinkers. But there are differences of opinions from the thinker in interpretation of Sunnah about the time of prayer. For example,there is a difference opinion between Syafi’i and Hanafi about the end of prayer time for Ashar.